SVD in Greece - Στοφόρος, Ε.; Μαστρογιάννη, Μ.; Άξιώτης, Ι.; Ζαφειρίου, Γ.; Χατζής, Θ.; Γεωργακόπουλος, Κ. (Journal of the Hellenic Veterinary Medical Society, 2019)
The Epidemiological data concerning the first outbreak of Swine Vesicular disease in Greece are reported. The morbidity rate was ten per cent. The swill fed pigs and the movement og the pigs have been the mode of transmission